Penatalaksanaan Diet Untuk Mengurangi Komplikasi Pada Penderita Diabetes Melitus Di Puskesmas Polokarto - FERIANA, ERRA, Supratman, Ph.D (2016)
Diabetes mellitus is a kind of disease which can interfere all organs of the body and cause a variety of complaints. Diabetes mellitus is not an infectious disease, however, the prevalence of this disease is increasing each year. This disease require for the proper management. There are four steps in the management, including diabetes treatment, physical exercise, education and right diet plan. There have been many patients with diabetes mellitus type 2 who encounter many kinds of obstacles during the treatment of the disease, especially problem associated with diet. The author's purpose is to discuss diabetes mellitus and nursing care. Here, the writer applied descriptive method as the the data collecting techniques. It was obtained through interview, observation, and literature study. The writer obtained the case from the regional area Polokarto health center service on March 28th to April 2nd, 2016. The assessment was done to Mr.H's family who suffer from Diabetes since three years ago. Mr. H did not recognized the certain symptoms of diabetes. There are complications of hypertension that occurred since the second year after Mr. H knowing his illness.Mr. H regularly check his blood sugar but every Mr. H is still drinking sweet tea everyday. When eating Mr. H reduce the rice portion, but he sometimes eat with more portion of rice if he likes the dish. Blood sugar tests obtained before management was 163 mg/ dl. The writer diagnosed the patient as ineffective management of therapeutic program due to patient's lack of knowledge. The management plan was discussed with the patient's family, such as diet management to reduce complications in the patients with diabetes mellitus. On Thursday, March 31st,,2016, given health education about signs and symptoms, complications, diet for diabetes mellitus and demonstrated diabetic foot gymnastics. Long-term goals, a sick family member is able to implement the program of therapeutic diet diabetes mellitus with psychomotor responses to standard patients were able to avoid foods that should not be consumed by people with diabetes mellitus . The term goals do health education, after the implementation of nursing sick family members were able to understand more about the management of diet in patients with diabetes mellitus, alsoable to understand the causes and complications diabtes mellitus with verbal responses and the standards of family members able to mention again about causes, complications and treatment of diet on diabetes mellitus. The family members has given a good response on the actions performed. The family were cooperative and able to explain back the health education materials that has been given. The family stated that they will implement proper diet for Mr. H.